Astaxanthin attenuates irradiation-induced osteoporosis in mice by inhibiting oxidative stress, osteocyte senescence, and SASP. Issue 22 (26th October 2022) - Geng, Qinghe; Wang, Shen; Heng, Ke; Zhai, Juan; Song, Xingchen; Xia, Lei; Wang, Lulu; Lin, Qiang; Li, Hongwei; Guo, Yilong
Abstract : Astaxanthin can correct osteoporotic phenotypes, caused by irradiation, by inhibiting oxidative stress, DNA damage, osteocyte senescence and SASP, subsequently promoting osteoblastic bone formation and inhibiting osteoclastic bone resorption. Abstract : Radiation therapy (RT) is a crucial part of many treatment plans for cancer patients. However, major undesired side effects are associated with this treatment, including impaired bone remodeling and bone loss. Irradiation induces bone loss due to promoted osteoclastic bone resorption and reduced osteoblastic bone formation. Astaxanthin (AST) is a natural antioxidant with anti-oxidative and anti-aging properties. However, it is unclear whether AST is also protective against osteoporosis induced by ionizing radiation (IR). Here, we evaluate the efficacy of AST in mitigating IR-induced bone loss in a mouse model where both hindlimbs received radiation. Reduced BMD, bone biomechanical strength, bone formation, elevated oxidative stress, and osteoclast activity with microarchitectural deterioration of trabecular and cortical bones were observed in IR mice. Supplementation with AST corrected these osteoporotic phenotypes, caused by IR, by inhibiting oxidative stress, DNA damage, osteocyte senescence, and senescence-associated secretory phenotype (SASP), subsequently promoting osteoblastic bone formation and inhibiting osteoclastic bone resorption. The results from our study provide experimental evidence for the clinical use of AST to prevent IR-induced osteoporosis in cancer patients.